1992
DOI: 10.1080/09670879209371719
|View full text |Cite
|
Sign up to set email alerts
|

The lesion nematodePratylenchus goodeyian important pest ofEnsetein Ethiopia

Abstract: The lesion nematode, Pratylenchus goodeyi, has been found to be a major problem of ensete (Ensete ventricosum) in Ethiopia, and is also recorded on banana and in association with the bacterial wilt disease caused by Xanthomonas campestris pv. musacearum. The implications of this bacterial/nematode complex are potentially serious for both crops, but especially for ensete, which is a starch staple for about 7 million people in Southern Ethiopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Sher & Allen, 1953 Pathogenic to banana and forms disease complex with bacterial wilt pathogens (Peregrine & Bridge, 1992;Pattison et al, 2002;Talwana et al, 2003). Associated with grapevine, strawberry and other crops (Castillo & Vovlas, 2007).…”
Section: Pratylenchus Goodeyimentioning
confidence: 99%
“…Sher & Allen, 1953 Pathogenic to banana and forms disease complex with bacterial wilt pathogens (Peregrine & Bridge, 1992;Pattison et al, 2002;Talwana et al, 2003). Associated with grapevine, strawberry and other crops (Castillo & Vovlas, 2007).…”
Section: Pratylenchus Goodeyimentioning
confidence: 99%
“…Wondimagegne (1981) reported that among the commonly observed insects in enset fields, the leafhopper (Poecilocarda nigrinervis Stal) seems to be a potential vector due to its active flying ability. The leaf streak nematode and the root lesion nematode have also been postulated to be associated with bacterial wilt (Pergrine and Bridge, 1992;Swart et al, 2000). Since cultivated enset is harvested before flowering, transmission of the disease via inflorescences, as is the case in banana, doesn't occur.…”
Section: Introductionmentioning
confidence: 99%
“…However, this production is threatened by among other factors Xanthomonas wilt (XW) caused by Xanthomonas vasicola pv. musacearum (Yirgou and Bradbury, 1968;Ashagari, 1985;Peregrine and Bridge, 1992;Tessera and Quimio, 1994). XW has been endemic to Ethiopia infecting enset and banana for over 50 years and was first reported and described in late 1960's (Yirgou and Bradbury, 1968;1974).…”
Section: Introductionmentioning
confidence: 99%